History Of The Constitution Of The Democratic Republic Of Timor Leste - Querubin Jong Ferreira (Fakultas Hukum, Universitas Warmadewa, 2025)
The historical record of the emergence of a constitutional state is actually a long and always interesting historical process to study. One such example is the history of the birth of the RDTL constitution from 1975 to 2002, which continues to be a topic of academic discussion and debate. The issue of the birth of the RDTL state constitution is a hot topic of discussion and interest, and has become a research topic for students of the Faculty of Law, both undergraduate and graduate. The debate that until now is still questioned even though in reality the 1975 constitution is only considered an official state document and at the same time becomes the foundation of state life, this becomes controversial because the drafters of the text and the preparatory council for the independence of the RDTL state were carried out through the election of the constituent assembly which had the authority at that time, to form and reformulate a new constitution, because the results and ideas of the 1975 constitution were considered to have no progress so that the election of the constituent assembly council was re-enacted to prepare for the independence of the state through the results of the referendum which was carried out simultaneously with the restoration of independence and at the same time the ratification of the new RDTL constitution by de jury on May 20, 2002. Although de facto the independence of the RDTL state on November 28, 1975 was only considered as a unilateral declaration. This legal issue is a serious debate and is always questioned about the existence of the 1975 constitution, under where, so that researchers use the word Qou vadis history of the RDTL constitution as an opening in this writing. By using the normative legal research method, which focuses on the study of authoritative state legal products, using several approaches, such as historical, conceptual, and applicable statutory approaches. However, this legal writing is still far from expectations, as it is limited to academic discussions.